Evolutionary Stability in Stochastic Environments (CSIAM Transactions on Life Sciences, 2025)
Evolutionary stability (or evolutionarily stable strategy) is the core concept of evolutionary game theory. Although evolutionary game theory has achieved great success in evolutionary biology, economics and social science, etc. over the past forty years, how to understand the impact of environmental stochastic fluctuations on the evolutionary stability is still one of the most challenging issues in evolutionary game theory. This paper mainly introduces the recent advances in the study of stochastic evolutionary stability and stochastic Nash equilibrium within the framework of stochastic evolutionary game dynamics. These studies may provide a possible way to better understand the complexity of evolutionary game dynamics in real world situations.